2008
DOI: 10.1590/s0102-86502008000700023
|View full text |Cite
|
Sign up to set email alerts
|

The influence of treatment access regulation and technological resources on the mortality profile of acute biliary pancreatitis

Abstract: PURPOSE: The influence of treatment access regulation and technological resources on the mortality profile of acute biliary pancreatitis (ABP) was evaluated. METHODS: The cases seen in a tertiary hospital were studied during two periods of time: 1995-1999 and 2000-2004, i.e., before and after the implementation of medical regulation. RESULTS: Among the 727 patients with acute pancreatitis, 267 had ABP and were classified according to APACHE II scores. The cases being referred to the tertiary hospital decreased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 14 publications
(21 reference statements)
0
3
0
4
Order By: Relevance
“…The need to identify cost-effective strategies to prevent and treat acute pancreatitis has been emphasized [26-28] and our study underlines this. In agreement with previous studies [5] we found that CFR (and SMR) decreased in recent years.…”
Section: Discussionmentioning
confidence: 62%
“…The need to identify cost-effective strategies to prevent and treat acute pancreatitis has been emphasized [26-28] and our study underlines this. In agreement with previous studies [5] we found that CFR (and SMR) decreased in recent years.…”
Section: Discussionmentioning
confidence: 62%
“…Na avaliação de 267 casos de PAB tratado no Hospital das Clínicas de Ribeirão Preto entre 1995 a 2004, a mortalidade geral foi de 11,6%, pouco acima do limite superior registrado na literatura para a pancreatite aguda quando se considera todas as etiologias (variação de 2 a 9%). Na PAB branda a mortalidade geral observada foi de 3,8%, 41 semelhante aos achados da literatura, em média, de 3%, com variação de 1 a 7%. 43 Nesse estudo, a mortalidade geral para a PAB grave foi de 27,9%, 39 e está dentro dos limites observados na literatura; de 8% a 39%, com média de 17%.…”
Section: 14-pancreatite Aguda Biliarunclassified
“…Within the context of the dynamic and diverse course of ABP patients with different care needs and of the management of patient flow, the definition of priorities and the appropriate access to services, resources and specialists are a challenge and may impair the application of the clinical decisions recommended in protocols and consensuses [19,[42][43][44][45] . Conservative treatment of ABP with cholangitis, similar to what occurs in cases without cholangitis, shows rates of spontaneous clearance of the common bile duct within two weeks of approximately 70%.…”
Section: Resultsmentioning
confidence: 99%
“…However, a response to clinical treatment occurs in 80% of cases and the need for urgent biliary disobstruction is rare [40,41] . These observations coupled with the characteristics of public health systems and possible access to a reference hospital and its services have definitely influenced the management of ABP cases associated with and without cholangitis [42,43] .…”
Section: Different Presentations Of Acute Biliary Pancreatitis and Almentioning
confidence: 99%